Utility of Soil Survey Data for Land Reclamation and Environmental Protection Programmes in Ghanshyampur and Purusottampur OCP of Eartern Coal Fields Ltd. of Distt. Burdwan, West Bengal State Concern for protection of the environment - Ali, Sharafat; Gawande, S.P. (Journal of Soil and Water Conservation, 2022)
Concern for protection of the environment is relatively of recent origin, in India. The developing countries, the world over, have the problem of scarce financial resources with inherent constraints for implementing effec- tive environmental protection measures. The Stockholm Conference on Human Environment (1972) and the Habitat U.N. Conference on Human Settlements held at Vancouver from May 31-June 11 1976 have focussed the need for global approaches and efforts towards environmental planning ai- med at improvements in human environment andqualitative improvement in life style of people.